(untitled) (Bangladesh Journal of Medical Science, 2024)
Background: The most prevalent form of birth defect is hypodontia, or the lack of teeth. Patients who suffer from agenesis of the maxillary lateral incisors worry about how their new teeth and face will look after therapy. The main purpose of orthodontic treatment, known as gap closure, is to preserve as many teeth as possible. The two most important methods regarding gap closure are mesialising canines and prosthetic implants. Objective: Mesialising canines and prosthetic implants for lateral maxillary incisor gap closure are the subjects of this systematic study. Methodology: In addition to using a systematic search technique on Google Scholar, PUBMED, and the Web of Science, we formally included or excluded studies, extracted data, assessed validity, and evaluated quality. A systematic review was conducted on all of the studies. In order to evaluate the quality, the Cochrane risk of bias tool was utilized. Results: According to our set inclusion criteria, 11 most relevant studies were found in the databases. Data was extracted from each study separately in an Excel Sheet. All studies mentioned discussed the use of the two best potential treatments, their advantages and disadvantages, and the parameters determining the best treatment. Conclusion: Although prosthetic implants did enhance a few metrics, this comprehensive study did not find a statistically significant difference between the two treatments. The comparative efficacy of two methods for closing the space left by removing maxillary lateral incisors requires more study. Bangladesh Journal of Medical Science Vol. 23 No. 03 July’24 Page : 765-774